Assessment of the Legal Instruments Used to Support the Tourism Sector in Poland During the Covid19 Pandemic - Bartosz Rymkiewicz (Communications of International Proceedings, 2022)
The SARS-CoV-2 (Covid-19) virus pandemic had a huge impact on the entire global economy. Restrictions introduced by state governments were particularly severe. Movement bans, restrictions on crossing the border and temporary bans or restrictions on the possibility of doing business in certain industries have had a very detrimental effect on the financial condition of many enterprises. The industry particularly affected by the effects of the pandemic was the tourism industry, which was affected both by the decreased interest in organized leisure by travelers and by the introduced restrictions and bans. Many economic entities found themselves in an unprecedented situation that prevented their actual functioning. The deprivation of the possibility of obtaining income, as well as the need to incur fixed costs, have shaken the financial liquidity of many entrepreneurs. Among entrepreneurs in the tourism industry, the effects of the SARS-CoV-2 virus epidemic particularly affected tour operators, which was related to specific legal regulations regulating their activities. The necessity to cancel most of the tourist events and the inability to organize new ones had a negative impact on the financial situation of many tourist entrepreneurs. The risk of mass bankruptcy of tourist enterprises forced legislators to introduce new legal solutions aimed at their protection. The purpose of this article is to present and evaluate the effectiveness of the most important solutions introduced by the Polish legislator. For this purpose, research methods were used, i.e. legal analysis and comparative analysis.
Keywords: tourism industry during the SARS-CoV-2 pandemic; legal solutions to protect tourism entrepreneurs; tourism organizers and Covid-19